A Conceptual Model for Adaptation of eHealth Standards by Low and Middle-Income Countries - Alunyu, Andrew Egwar; Nabukenya, Josephine (Journal of Health Informatics in Africa, 2018)
Background and Purpose: Electronic health (ehealth) is the use of information and communication technology to support healthcare. It is used to driving efforts to achieve sustainable development goals (SDGs) particularly “good health and well-being for all”. Nonetheless, just like other technologies, ehealth has rapidly gained ground in low and middle-income countries (LMICs) although with scanty government intervention. In fact, governments in LMICs have only lately developed ehealth strategies. Much as ehealth offers the promise for improved and affordable healthcare and service delivery, its success is still dependent on the specifications (standards) to support interoperability and information exchange. Regrettably, standardization efforts in LMICs are greatly curtailed by resource constraints.Methods: We reviewed literature on ehealth standardisation in LMICs using four African countries as our case studies. The objective of the study was to explore the challenges of ehealth standards development and or adoption by LMICs and posit that adaptation of existing international ehealth standards is a better option for LMICs. Qualitative analysis was used to derive key themes.Results: Our study findings indicate several challenges to ehealth standardization in LMICs including delayed standardisation efforts and unregulated penetration of ehealth, slight industry involvement, inadequate funding for the standardisation process, insufficient human resources, less to none participation in the international standards development process, and inadequate technical infrastructure for standards participation among others.Conclusions: This study recommends adaptation of international ehealth standards to local context of individual LMICs to help streamline both patient data and health information sharing. To achieve this, we developed the ehealth standards adaptation model. The model offers better opportunity to fast-track ehealth standardisation efforts in LMICs, as such creating an enabling platform for ehealth systems interoperability and support for health information exchange.